2020
DOI: 10.3390/toxins12100646
|View full text |Cite
|
Sign up to set email alerts
|

Ankle and Foot Spasticity Patterns in Chronic Stroke Survivors with Abnormal Gait

Abstract: Chronic stroke survivors with spastic hemiplegia have various clinical presentations of ankle and foot muscle spasticity patterns. They are mechanical consequences of interactions between spasticity and weakness of surrounding muscles during walking. Four common ankle and foot spasticity patterns are described and discussed through sample cases. The patterns discussed are equinus, varus, equinovarus, and striatal toe deformities. Spasticity of the primary muscle(s) for each deformity is identified. However, it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 20 publications
1
30
0
Order By: Relevance
“…Passive ankle ROM was not different between low and high spasticity groups. A previous study has reported that a higher spasticity was associated with higher limitations in the passive ROM ( Li, 2020 ). In this study, both the low and high spasticity group had significant restricted ankle passive ROM.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Passive ankle ROM was not different between low and high spasticity groups. A previous study has reported that a higher spasticity was associated with higher limitations in the passive ROM ( Li, 2020 ). In this study, both the low and high spasticity group had significant restricted ankle passive ROM.…”
Section: Discussionmentioning
confidence: 97%
“…This suggests that the ankle passive ROM is influenced by ankle muscle spasticity regardless of spasticity intensity. Spasticity, weakness of ankle muscles, and muscle contracture may explain the limited ankle passive ROM in both groups ( Mecagni et al, 2000 ; Li, 2020 ).…”
Section: Discussionmentioning
confidence: 98%
“…The sample size was small and only the gastrocnemius muscle was injected. So, we have no information about the other muscles involved in the spastic equinus/equinovarus pattern, such as the soleus, tibialis posterior, flexor digitorum (longus and brevis), flexor hallucis (longus and brevis), extensor hallucis longus and tibialis anterior [ 14 ]. The study did not include a long-term timeline of serial (clinical and ultrasonographic) evaluations after the onset of stroke or BoNT-A treatment, except for follow-up evaluation at 1 month after BoNT-A injection.…”
Section: Discussionmentioning
confidence: 99%
“…69 However, clinical presentation of poststroke gait varies depending on severity of spasticity, involvement, and distribution of spastic muscles. 69,73,74 Another example is shown in Figure 2A. Spastic equinovarus of the ankle and foot localizes weight-bearing on the lateral foot, undoubtedly causing calluses and pressure sores over time.…”
Section: Neuromechanical Consequencesmentioning
confidence: 99%